Effect of Cu2 +-complexation on the scavenging ability of chrysin towards photogenerated singlet molecular oxygen (O2(1Δg)). Possible biological implications - Muñoz, Vanesa Alejandra (2016)
Visible-light irradiation of aqueous-ethanolic solutions of Riboflavin (Rf) in the individual presence of the flavone chrysin (Chr) and its complex with Cu2 + ([Chr2Cu]; 2:1 L:M) generates singlet molecular oxygen O2(1Δg), that concomitantly interact with both flavone derivatives. Overall (kt) and reactive (kr) rate constants in the order of 107 M− 1 s− 1 were determined for the process. Metal chelation greatly enhances the scavenging ability of [Chr2Cu] towards O2(1Δg) through a mechanism dominated, in > 80%, by the physical component. In this way, practically all O2(1Δg) is deactivated by the complex without significant loss of the quencher. The isolated flavone quenches O2(1Δg) in a prevailing reactive fashion. The very low value exhibited by [Chr2Cu] for the kr/kt ratio constitutes a positive quality for antioxidative protectors in biological media, where elevated local concentration and high reactivity of significant molecules make them initial targets for O2(1Δg) aggression. Finally, two interesting properties in the field of free radicals scavenging by [Chr2Cu] must be mentioned. In first place metal chelation itself, in the obvious sense of free metal ion withdrawal from the oxidizable medium, prevents the initiation of a free radical-mediated oxidation processes through mechanisms of Fenton or lipid peroxidation. In addition, the incorporation of Cu adds to [Chr2Cu] the ability of a free radical scavenger, already described for similar Cu-chelate compounds. This collection of beneficial properties positions the complex as a remarkably promising bioprotector towards ROS-mediated oxidation. A quantification of the efficiency on the initial anti-oxidative effect exerted by Chr and [Chr2Cu] towards tryptophan was carried out. The amino acid is an archetypal molecular model, commonly employed to monitor oxidative degradation of proteinaceous media. It was efficiently photoprotected against O2(1Δg)-mediated photooxidation by [Chr2Cu].